Performance of Nellore females in tropical pastures during the rainy season when supplemented with molasses blocks - Henrique Moreira Lopes; Maria Lucia Pereira Lima; Gabriel Carletti Zilião; João Alberto Negrão; Flávia Fernanda Simili; Bianca Vilela Pires; Lenira El Faro (Semina: Ciências Agrárias, 2019)
The objective of this study was to measure the effect of supplementation with molasses blocks compared with conventional mineral supplementation (with specific formulations for the rainy and dry season) in 92 7-month-old Nellore heifers (Experiment 1) and 40 primiparous 31-month-old Nellore cows (Experiment 2) in Marandu grazing areas. The following measurements were obtained: weight, supplement intake, blood urea and glucose in heifers (Experiment 1), supplement intake, cow weight, body score, calf weight and ruminal temperature and drinking events in primiparous females (Experiment 2). The average molasses block intake was 242 g day-1 per heifer, with an average weight gain of 0.290 kg day-1; the heifers who consumed the molasses blocks were heavier during the rainy season (P < 0.05; Experiment 1). In Experiment 2, molasses block intake varied from 77 to 821 g day-1 per primiparous female, and the average intake in the control group was between 100 and 370 g day-1. The primiparous females given molasses blocks displayed lower weight loss due to calving (P < 0.05) and retained higher body scores at 150 days postpartum (P < 0.05). Ruminal temperature (P < 0.05) and drinking events (P < 0.05) were higher in primiparous Nellore females given molasses blocks. Overall, molasses blocks effectively increased Nellore female performance during the rainy season in Marandu grass pastures.